2020
DOI: 10.1146/annurev-cancerbio-030419-033541
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Chromosome Segregation and Cancer

Abstract: The mitotic spindle assembly checkpoint (SAC) is an intricate cell signaling system that ensures the high fidelity and timely segregation of chromosomes during cell division. Mistakes in this process can lead to the loss, gain, or rearrangement of the genetic material. Gross chromosomal aberrations are usually lethal but can cause birth and development defects as well as cancer. Despite advances in the identification of SAC protein components, important details of the interactions underpinning chromosome segre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 161 publications
(149 reference statements)
1
6
0
Order By: Relevance
“…We found a signature composed of genes important for mitotic spindle assembly (HALLMARK_MITOTIC_SPINDLE) to be statistically significant and robust to sample exclusion for early-stage lung tumors with BEANIE, consistent with prior studies. 18 Another signature comprised of genes encoding proteins involved in glycolysis and gluconeogenesis (HALLMARK_GLYCOLYSIS) was also found to be statistically significant and robust to sample exclusion for the early-stage tumors with BEANIE, which is in agreement with a prior study 19 describing an association between TKI treatment and its effect on decreased activity of glycolysis. Furthermore, the top constituent genes for both of these signatures were consistently upregulated across all samples (Fig.…”
Section: Group Biology Analysis Of Distinct Clinical States In Non-small Cell Lung Carcinomasupporting
confidence: 86%
“…We found a signature composed of genes important for mitotic spindle assembly (HALLMARK_MITOTIC_SPINDLE) to be statistically significant and robust to sample exclusion for early-stage lung tumors with BEANIE, consistent with prior studies. 18 Another signature comprised of genes encoding proteins involved in glycolysis and gluconeogenesis (HALLMARK_GLYCOLYSIS) was also found to be statistically significant and robust to sample exclusion for the early-stage tumors with BEANIE, which is in agreement with a prior study 19 describing an association between TKI treatment and its effect on decreased activity of glycolysis. Furthermore, the top constituent genes for both of these signatures were consistently upregulated across all samples (Fig.…”
Section: Group Biology Analysis Of Distinct Clinical States In Non-small Cell Lung Carcinomasupporting
confidence: 86%
“…Mistakes in the cell division process can lead to rearrangement, loss or gain of chromosomes, genome instability and cancers. 30 Therefore, the molecular function of BUB1 and BUB1B genes in HD cancers should be further examined. Several experimental and bioinformatic studies have shown the importance of EXO1 in replication, DNA repair pathways, cell cycle checkpoints, and its association to cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The SAC plays a fundamental role in maintaining genome stability by ensuring the timely segregation of the genetic material at every cell division. Mistakes in the cell division process can lead to rearrangement, loss or gain of chromosomes, genome instability and cancers 30 . Therefore, the molecular function of BUB1 and BUB1B genes in HD cancers should be further examined.…”
Section: Discussionmentioning
confidence: 99%
“…In this set of experiments, we define P = {x|x 7 = 1} \ U , where \ denote the set difference operator. In fact, x 7 = 1 denotes the network states with expressed Cdc20, whose overexpression has been reported in breast, lung, gastric, and pancreatic cancers [21]. Therefore, our second objective for deriving the IBR structural intervention is…”
Section: Quantifying the Multi-objective Cost Of Intervention In Uncertain Gene Regulatory Networkmentioning
confidence: 99%